Construct Validity of the “Motives for Physical Activity Measure-Revised” (MPAM-R) Questionnaire in a Sample of Greek Secondary School Pupils - Lazaridis, Αλέξανδρος; Digelidis, Νικόλαος; Krommydas, Χαράλαμπος (Inquiries in Physical Education and Sport, 2019)
The adolescence is particularly important as young people shape lifestyles that will follow them later. The purpose of this study was to adapt the “Motives for Physical Activity Measure-Revised” questionnaire (MPAM-R; Ryan, Frederick, Lepes, Rubio, & Sheldon, 1997) in the Greek language. The sample consisted of 345 second-ary school boys (N = 147) and girls (N = 198), aged 12 to 15 years old (Mage: 13.78 ± .85 years). Confirmatory Factor Analysis (CFA) revealed acceptable model fit index after removing six items due to high loadings with other items (χ2242 = 586.93, TLI = .906, CFI = .917, RMSEA = .064, RMSEA 90% CI = .058 - .071). Cronbach’s α index also showed acceptable internal consistency in all the examined scales (α = .79 to .89; Interest/Enjoyment, Competence, Appearance, Fitness, Social). Further statistical analyses revealed significant differences οn Interest/Enjoyment (F2,336 = 5.740, p < .01) between age groups. Younger pupils had significantly higher scores on Interest/Enjoyment compared with the older ones. The use of MPAM-R tool (Ryan et al., 1997), adapted to the Greek language, can contribute to a more meaningful assessment of the motives that encourage adolescents to participate in physical activities. Finally, it can be useful for the Physical Education teacher to evaluate students’ motives towards participation in out-of-school physical activities.